2009
DOI: 10.1016/j.tins.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution: mechanisms of neuroinflammation and CNS disease

Abstract: Emerging evidence implicates air pollution as a chronic source of neuroinflammation, reactive oxygen species (ROS), and neuropathology instigating central nervous system (CNS) disease. Stroke incidence, and Alzheimer’s and Parkinson’s disease pathology are linked to air pollution. Recent reports reveal that air pollution components reach the brain. Further, systemic effects known to impact lung and cardiovascular disease also impinge upon CNS health. While mechanisms driving air pollution-induced CNS pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
998
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,269 publications
(1,032 citation statements)
references
References 102 publications
(153 reference statements)
26
998
0
8
Order By: Relevance
“…Those particles of nanoscale dimensions, requiring analysis by transmission rather than scanning electron microscopy, have, until recently, received less attention than the larger, often more heterogenous spherules. Magnetite nanospheres up to ≾ 200 nm can have a direct entry route to the brain through the axons of the olfactory nerve, as suggested by experimental studies on carbon (29) and TiO 2 nanoparticles (30), and the reported presence of NPs in the olfactory bulb of some Mexico City cases (14,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 96%
“…Those particles of nanoscale dimensions, requiring analysis by transmission rather than scanning electron microscopy, have, until recently, received less attention than the larger, often more heterogenous spherules. Magnetite nanospheres up to ≾ 200 nm can have a direct entry route to the brain through the axons of the olfactory nerve, as suggested by experimental studies on carbon (29) and TiO 2 nanoparticles (30), and the reported presence of NPs in the olfactory bulb of some Mexico City cases (14,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 96%
“…Siddique et al (2011) compared children living in the New Delhi (India) urban area with children living in rural areas and showed that ADHD was positively correlated with current PM 10 levels. Air pollutants may induce systematic inflammation, which could be a possible mechanism mediating these effects (Block & Calderon-Garciduenas, 2009;Calderon-Garciduenas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2009; Farhat et al, 2011), central nervous system disorders (Sunderman, 2001;Kreyling et al, 2006;Block and Calderon-Garciduenas, 2009;Pearson et al, 2010;Wang et al, 2012) and diabetes (Andersen, 2012;Andersen et al, 2012). Since many of these health conditions are interlinked, comprehensive studies are required to better understand the impact of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%